2016
DOI: 10.1007/s13197-016-2234-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gelatinized-retrograded and extruded starches on characteristics of cookies, muffins and noodles

Abstract: The effect of substitution of wheat flour with gelatinized-retrograded starch (GRS) and extruded starch (ES) at 10 and 20 % levels on characteristics of cookies, muffins and noodles was evaluated. Cookies made by substitution of flour with GRS or ES were lighter in color, showed higher spread ratio and resistant starch (RS) content. Muffins made by substitution of flour with GRS or ES were lighter in color, showed less height, specific volume and gas cells and higher RS content. Muffins containing GRS were les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…According to Sajilata et al (2006), resistant starch improves product characteristics including crispness, expansion, mouthfeel, color, and flavor. Sharma et al (2016) also found that substitution in cookies with gelatinized-retrograded starch and extruded starch have lower rupture force compared to non-substituted cookies. This finding could be attributed to the higher resistant starch content in substituted cookies.…”
Section: Physical Propertiesmentioning
confidence: 83%
“…According to Sajilata et al (2006), resistant starch improves product characteristics including crispness, expansion, mouthfeel, color, and flavor. Sharma et al (2016) also found that substitution in cookies with gelatinized-retrograded starch and extruded starch have lower rupture force compared to non-substituted cookies. This finding could be attributed to the higher resistant starch content in substituted cookies.…”
Section: Physical Propertiesmentioning
confidence: 83%
“…A decreased hydration of amorphous regions leading to reduced granular swelling was reported for annealed corn and wheat starches (Tester and Morrison 1990;Zavareze and Dias 2011). Reduction in CL in wheat flour noodles fortified with gelatinized-retrograded starch with enhanced resistant starch (RS) content has been reported (Sharma et al 2016). Lower swelling rate has been reported for MBS-SPS (20:80) blended noodles, which was approximately 1.84 after 1 h of cooking (Thao and Noomhorm 2011).…”
Section: Cooking Behaviormentioning
confidence: 87%
“…This could be due to the protein dilution and lower amount of wheat flour starch in the flour-RS blends, which decreased the amount of reducing sugar and amino acids available for the Maillard reaction during baking, resulting in slightly lighter and less reddish bread crusts. Sharma et al (2016) reported that cookies and muffins prepared by substitution of wheat flour with RS were lighter in color compared to those made without substitution, attributing this to the dilution of protein.…”
Section: Bread Characteristicsmentioning
confidence: 99%
“…This starch fraction has some advantages over conventional fibers when added to food products. Due to its white color, neutral flavor, and small particle size, RS can be used without significantly altering the sensory characteristics of the product (Sharma et al 2008(Sharma et al , 2016, and can be used either alone or combined with other fibers in different food products. However, the amount of RS used to replace flour depends on the starch type being used, the food type, and the desired fiber level (Sharma et al 2016).…”
Section: Introductionmentioning
confidence: 99%